Observations of Clouds and Radiation over King George Island and Implications for the Southern Ocean and Antarctica - Cordero-Carrasco, R (American Geophysical Union, 2025)
Clouds play an important role in the Southern Ocean and Antarctic surface energy balance via their radiative effects and in surface mass balance via precipitation formation. Here, we use measurements at Escudero Station (62.2 degrees S, 58.97 degrees W) on King George Island, north of the Antarctic Peninsula, to characterize clouds and their effects on the surface incoming radiation between 2017 and 2023. These measurements are unique providing 7 years of simultaneous cloud and radiation measurements, including year-round observations. Cloud measurements using a mini micropulse lidar showed that clouds are present 96% of the time with persistent low-level supercooled liquid-containing clouds: 86% of the lowest cloud bases are within the first 1 km. Liquid was present about 80% of the time, and most liquid was supercooled: cloud-base temperatures were below 0 degrees C for 82% of atmospheric columns classified as liquid-containing. Combining pyranometer and pyrgeometer measurements with clear-sky radiative transfer modeling, we find that the downward cloud radiative forcing is negative during October-March and positive during April-September. For clouds with base temperatures below 260 K, downward longwave cloud forcing is found to be lower for ice-only clouds than for liquid-containing clouds; however, at warmer temperatures, both ice-only and liquid-containing clouds exhibited similar radiative forcing. During strong atmospheric river (AR) events, when long corridors of moisture bring heat and precipitation, surface temperatures are found to be positively correlated with downward shortwave (DSW) cloud forcing in summer, indicating that weaker DSW cloud forcing is linked to higher summertime surface temperatures.